Formulasi dan Uji Aktivitas Gel Antisariawan Ekstrak Daun Alpukat (Persea americana Mill.) Secara In vivo Pada Tikus Putih - Taufik Septiyan Hidayat; Rosi Kustiani; Gioamanda Dwi Sumarni (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Oral ulceration is a common disorder that causes pain and can interfere with daily activities. Avocado (Persea americana Mill.) leaves contain bioactive compounds that may support wound healing. This study optimized a gel formulation containing avocado leaf extract and evaluated its anti-ulcer activity in male Wistar rats. The extract was prepared by maceration with 96% ethanol and formulated into carbopol-based gels. Twenty-four rats were randomly allocated to four groups (n = 6): negative control, positive control, gel base, and the selected avocado leaf extract gel. Oral ulcers were induced with 50% acetic acid and evaluated macroscopically; one blinded tissue sample from each group was assessed histopathologically. Phytochemical screening detected alkaloids, flavonoids, tannins, saponins, and steroids/triterpenoids. The selected gel produced a higher macroscopic healing score than the negative control and gel-base groups on day 7, although the positive control showed the highest score. Histopathological observations supported improved epithelial regeneration in the selected-formula group. Kruskal–Wallis analysis showed a difference among groups (p < 0.001), and the prespecified comparison between the negative control and selected formula was significant (p = 0.004). These findings indicate that avocado leaf extract gel warrants further investigation as a topical candidate for oral-ulcer healing.